Studies of Endocrine Disruptors: Nonylphenol and Isomers in Biological Models (2023)
Abstract Certain emerging pollutants are among the most widely used chemicals globally, causing widespread concern in relation to their use in products devoted to cleaniness and asepsis. Nonylphenol ethoxylate (NPEOn) is one such contaminant, along with its degradation product, nonylphenol, an active ingredient presents in nonionic surfactants used as herbicides, cosmetics, paints, plastics, disinfectants, and detergents. These chemicals and their metabolites are commonly found in environmental matrices. Nonylphenol and NPEOn, used, are particularly concerning, given their role as endocrine disruptors chemical and possible neurotoxic effects recorded in several biological models, primarily aquatic organisms. Limiting and detecting these compounds remain of paramount importance. The objective of the present review was to evaluate the toxic effects of nonylphenol and NPEOn in different biological models. Environ Toxicol Chem 2023;00:1–12. © 2023 SETAC